(3fHPI aj CfSGH GdeYhdjs - (3CHh SdjeGf eMeO Hf YGeQ GdYOhj GdeYhdjs ((3SYjO Hf SdGe GdMQedi GdfNdi s)
(3ChdgG (B:s
(3hfSH eYhdI GdJi JfSH Edjg GdeYGhd , hgh eYhdI Hf TeS GHf YeQh Hf ZGfe Hf YKeGf Hf bMWGf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B210 - (3U(B219s
(3cJHgG GdfGSN dTjNI fGUQ GHf eMeO Hf Sja Hf CMeO Hf eMeO GdeYhdis
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B166 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs